UPI KKN Student Action in Desantri: Desa Sadar Nutrisi dan Gizi activities in Ciherang Village, Cianjur Regency - Fitri, Amelia; Tohaga, Puspa Auliani; Santoso, Rismawan Giri; Putra, Rio Mahesa (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
This article discusses stunting, a child growth problem caused by a lack of adequate nutrition, which is a severe issue in Indonesia, especially in rural areas. The research method used in this article is mixed methods. Universitas Pendidikan Indonesia (UPI) students are crucial in tackling this problem through the Desantri program in Ciherang Village, Cianjur Regency. This program aims to increase family nutrition awareness and reduce stunting rates. This involves nutrition counseling, monitoring of children's growth, and distribution of nutritional supplements. As a result, this program reduced the village's stunting rate. This article highlights the importance of good nutrition and adequate nutrition in preventing stunting and the critical role of students as agents of social change in overcoming this problem. The collaboration between students, health workers, and the community in this program shows that collaboration can effectively solve the problem of stunting in various regions, helping children grow healthily and setting a positive example for similar initiatives.